Ultrafine-grained boron carbide ceramics fabricated via ultrafast sintering assisted by high-energy ball milling. Issue 6 (15th April 2018) - Zhang, Xiaorong; Zhang, Zhixiao; Nie, Bin; Chen, Huanyu; Wang, Guangshuo; Mu, Jingbo; Zhang, Xiaoliang; Che, Hongwei; Wang, Weimin
Abstract: Ultrafine-grained boron carbide ceramics with ultrahigh hardness were fabricated via a unique combination of high-energy ball milling and self-propagating high-temperature synthesis plus quick pressing (SHS/QP) method. Results show that ultrafine powders obtained by milling possess a disordered character. During the SHS/QP, the tiny particles in the milled powders are integrated into neighbouring large particles to form ceramic grains. The average grain size of the ceramics is approximately 290 nm. After SHS/QP, a few amorphous areas and high-density defects were still observed in ceramics. The ceramics possess high relative density (approximately 99.2%) and ultrafine grain (approximately 290 nm) but with a weak degree of crystallinity which weakens hardness. Heat treatment can improve crystallinity while maintaining the ultrafine grain of the ceramics, thereby increasing the hardness of the ceramics from 31 GPa to 40 GPa.